2023
DOI: 10.1007/s13346-023-01440-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oral delivery of hesperidin-loaded sulfobutylether-β-cyclodextrin/chitosan nanoparticles for augmenting its hypoglycemic activity: in vitro-in vivo assessment study

Mona Ebrahim Elmoghayer,
Noha Mohamed Saleh,
Irhan Ibrahim Abu Hashim

Abstract: Hesperidin (Hsd), a bioactive phytomedicine, experienced an antidiabetic activity versus both Type 1 and Type 2 Diabetes mellitus. However, its intrinsic poor solubility and bioavailability is a key challenging obstacle reflecting its oral delivery. From such perspective, the purpose of the current study was to prepare and evaluate Hsd-loaded sulfobutylether-β-cyclodextrin/chitosan nanoparticles (Hsd/CD/CS NPs) for improving the hypoglycemic activity of the orally administered Hsd. Hsd was first complexed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 156 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…The results of molecular docking showed that nine active components had good binding ability with key protein INSR, including Ginkgolic acid (GA13:1), Ginkgolic acid (GA15:1), Gypenoside XXVII, Gypenoside XXVIII, Hesperetin, Nicotiflorin, Quercetin, Spinasterol and Gypenoside XVII. Recent studies show that hesperidin, quercetin and spinach sterol all have obvious therapeutic effects on diabetes [ 43 , 44 , 45 ], which further verifies the accuracy of screening active compounds by network pharmacology and molecular docking. In particular, we found that Gypenoside XVII could bind to six core proteins strongly, and the docking scores were high among the screened compounds.…”
Section: Discussionmentioning
confidence: 90%
“…The results of molecular docking showed that nine active components had good binding ability with key protein INSR, including Ginkgolic acid (GA13:1), Ginkgolic acid (GA15:1), Gypenoside XXVII, Gypenoside XXVIII, Hesperetin, Nicotiflorin, Quercetin, Spinasterol and Gypenoside XVII. Recent studies show that hesperidin, quercetin and spinach sterol all have obvious therapeutic effects on diabetes [ 43 , 44 , 45 ], which further verifies the accuracy of screening active compounds by network pharmacology and molecular docking. In particular, we found that Gypenoside XVII could bind to six core proteins strongly, and the docking scores were high among the screened compounds.…”
Section: Discussionmentioning
confidence: 90%